Tangut (Xi Xia) Studies in the Soviet Union: Quinta Essentia of Russian Oriental Studies - Dmitriev, Sergey (Mongolian Journal of International Affairs, 2015)
Grace to the famous discovery of Piotr Kozlov’s expedition, a very rich collection of various Tangut books in a mausoleum in the dead city of Khara-Khoto was found in 1908, and almost all the texts in the Tangut language were then assembled in Saint-Petersburg. Because of this situation Russian Tangutology became one of the most important in the world very fast, and Russian specialists, especially Alexej Ivanov, did the first steps to understanding the Tangut language and history, which had for a very long time been hidden from humanity. This tradition persisted in the Soviet Union. Nikolaj Nevskij in 1929 returned to Russia from Japan, where he had stayed after 1917, mainly to continue his Tangut researches. But in 1937, during Stalin’s Purge, he was arrested and executed, Ivanov too. The line of tradition was broken for almost twenty years, and only the 1960s saw the rebirth of Russian Tangutology. The post-War generation did a gigantic work, raising Tangut Studies to a new level. Unfortunately, they almost had no students or successors. The dramatic history of Tangut Studies in Russia could be viewed like a real quinta essentia of the fate of Oriental Studies in Russia – but all the changes and tendencies are much more demonstrative of this example. Mongolian Journal of International Affairs Vol.19 2014: 178-196